Optically Pumped Lasing Properties Of ZnO Nanorods - Nordin, Muhammad Nuri (2018)
The purpose of this study is to investigate the characteristics of optically pumped laser from the ZnO nanorods grown by using the two-step chemical bath deposition (CBD). Samples are grown on two types of substrates, glass and sapphire wafer, AI2O3. Various conditions and treatments of the samples have been introduced to observe the optical emission mainly by manipulating the thickness of ZnO seed layer thin film and the heat treatment condition. The procedures for CBD process is fixed for four hours at 97“C for growth process with the solutions of 0.05 M of zinc nitrate (Zn(NO.3)2.6H2O) and 0.05 M of hexamethylenetetramine (11 MT). Growth properties of the samples are characterized using field emission scanning electron microscopy (FESEM) and X-ray Diffraction (XRD). FESEM showed the morphology of grown nanorods with each sample having their own distinctive size, shape and population. XRD measurement revealed the information about the crystal structure of nanorods with a high visible peak at 20 34.4° showing the growth of nanorods is preferentially along the c-axis and calculation using the XRD data determined the crystallite size of crystal structure.